Clapping In Seventh-Day Adventist Worship - Wauran, Max H. (Klabat Theological Review, 2020)
Clapping is considered as a media of praise and thanks in Christian worship. Some give space to this practice while other reject it. This article tried to identify the biblical foundation of these ideas, and was carried out through the following phases: formulating the problem, preparing the title, and searching the related supporting materials in the library research and electronic facilities. The research focused on three main aspects: the clapping in the Bible, the Christian and practice of clapping in worship services, and clapping in Seventh-day Adventist Church. It is found that there is no Bible text and theological evidence which support the practice of clapping in the place of worship, in other words clapping in the church services is unbiblical, and for this reason clapping in Seventh-day Adventists worship services is not necessary. Instead of clapping, the use of amen is suggested in responding the message or musical presentation. Since clapping has become controversial issue in Adventist worship services, the church leaders need to instruct and guide the church members to the right understanding of clapping. Keywords: clapping; applaus; worship; praise